Question #2152

-0,044x³+2x²-50x+ax-600
Please solve for a and show calculations

Expert's answer

Let's try factorize this expression:

-0,044x³+2x²-50x+ax-600 = 2x²(-0,022x+1) +& (-50+a)x-600

Thus

-0.022 = (-50 + a)/(-600), -50 + a = 13.2, a = 63.2

Thus

2x²(-0,022x+1) +& 13.2x-600 = 2(-0,022x+1) - 600( - 0.022x +1) = 2 (x² -300)( - 0.022x +1)

-0,044x³+2x²-50x+ax-600 = 2x²(-0,022x+1) +& (-50+a)x-600

Thus

-0.022 = (-50 + a)/(-600), -50 + a = 13.2, a = 63.2

Thus

2x²(-0,022x+1) +& 13.2x-600 = 2(-0,022x+1) - 600( - 0.022x +1) = 2 (x² -300)( - 0.022x +1)

## Comments

## Leave a comment